Pharmacokinetics of oral transmucosal and intramuscular dexmedetomidine combined with buprenorphine in cats. Issue 2 (1st October 2014) - Porters, N.; de Rooster, H.; Bosmans, T.; Baert, K.; Cherlet, M.; Croubels, S.; De Backer, P.; Polis, I.
<x xml:space="preserve">Abstract</x> Plasma concentrations and pharmacokinetics of dexmedetomidine and buprenorphine after oral transmucosal (OTM) and intramuscular (i.m.) administration of their combination in healthy adult cats were compared. According to a crossover protocol (1‐month washout), a combination of dexmedetomidine (40 μg/kg) and buprenorphine (20 μg/kg) was given OTM (buccal cavity) or i.m. (quadriceps muscle) in six female neutered cats. Plasma samples were collected through a jugular catheter during a 24‐h period. Plasma dexmedetomidine and buprenorphine concentrations were determined by liquid chromatography–tandem mass spectrometry. Plasma concentration–time data were fitted to compartmental models. For dexmedetomidine and buprenorphine, the area under the plasma concentration–time curve (AUC) and the maximum plasma concentrations (Cmax) were significantly lower following OTM than following i.m. administration. For buprenorphine, time to reach Cmax was also significantly longer after OTM administration than after i.m. injection. Data suggested that dexmedetomidine (40 μg/kg) combined with buprenorphine (20 μg/kg) is not as well absorbed from the buccal mucosa site as from the intramuscular injection site.